Adaptive path following control for wave gliders in ocean currents and waves - Yu, Peiyuan; Zhou, Ying; Sun, Xiujun; Sang, Hongqiang; Zhang, Shuai (Ocean engineering, 2023)
In this paper, a design method is presented for path following control of wave gliders (WGs) subject to velocity and rudder input constraints, as well as marine currents and wave disturbances. The control method integrates an adaptive integral line-of-sight (AILOS) guidance law, an adaptive target-path-switching control and a modified incremental PID heading control for WGs with the multi-straight-line path following, which can extremely overcome the influence of such marine currents interference and guarantee path following accuracy. For the control loop, adaptive adjustments on the parameters of the lookahead distance and the error-circle radius are built to provide a current-influenced position error compensation suitable for the time-varying velocity of the WG. Additionally, an online wave filter using an extended Kalman filter (EKF) is developed to address the issue of wave-induced disturbance influence worked on the position and heading of the WG. Further, simulations and sea trials demonstrate both tracking accuracy and high robustness under ocean disturbances with rudder constraints. •Adaptive path-following control is for wave gliders subject to velocity, rudder input constraints, and marine disturbances.•Adaptive adjustments in AILOS and target-path-switching control are to compensate a current-influenced error.•An online wave filter is used for avoiding wave-induced disturbance worked on the position and heading.•Simulations and sea trials of the experimental wave glider were put forward.